The struggle for power - dynamics in the world hegemony of the United States and China - Culek, Jakub (2021)
This thesis deals with the power struggle between The United States of America and the People’s Republic of China. The main goal is to determine if China can substitute the U.S. as a world hegemon. A nation can achieve a state of hegemony through a combination of economic and military superiority. The first chapter presents different approaches to determining hegemony, described by different theories, each emphasizing various methods. The second chapter pays attention to the background of the U.S. and China. It describes each country's background in order to understand better the problems they are facing today. The last chapter evaluates each country’s position in different spheres of international relations, after which it is possible to decide if China has the capability to be a world hegemon.